1991
DOI: 10.3109/00365599109024541
|View full text |Cite
|
Sign up to set email alerts
|

Prostatectomy in Denmark:Regional Variation and the Diffusion of Medical Technology 1977-1985

Abstract: In many countries prostatectomy is one of the most common surgical operations in elderly men. We used administrative data for the entire male population of Denmark to study temporal and regional variations in the use of prostatectomy from 1977 to 1985. The total annual number of prostatectomies increased by 43% during the period, when the transurethral procedure (TURP) gradually replaced traditional open surgery. TURP accounted for 56% of all operations in 1977 but increased its share to 92% in 1985. Substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Prostatic hyperplasia is common in old men, 70-80% have at least microscopically verifiable hyperplasia [1], During the last decades transurethral prostatic resection (TURP) has become more frequent and in Denmark the treatment frequency today is 23/1,000 men over the age of 80 years [2] versus 11/1,000 in 1968 [3], In daily practice we therfore often meet with the dilemma whether or not to offer surgical treatment to an old patient with lower urinary tract symptoms (LUTS). Primarily one has to evaluate whether voiding problems are caused by infravesical obstruction, detrusor insufficiency or, as is often Material and Methods Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Prostatic hyperplasia is common in old men, 70-80% have at least microscopically verifiable hyperplasia [1], During the last decades transurethral prostatic resection (TURP) has become more frequent and in Denmark the treatment frequency today is 23/1,000 men over the age of 80 years [2] versus 11/1,000 in 1968 [3], In daily practice we therfore often meet with the dilemma whether or not to offer surgical treatment to an old patient with lower urinary tract symptoms (LUTS). Primarily one has to evaluate whether voiding problems are caused by infravesical obstruction, detrusor insufficiency or, as is often Material and Methods Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. Relative increase in total annual number of prostatec- [3], The preference for TURP over OP may be related to factors other than the lower peri-operative mortality and morbidity mentioned by Graham [4], Analysis of the Scottish patients included in the present study showed that a diagnosis of prostate or bladder cancer in the 3…”
Section: <0mentioning
confidence: 65%
“…In Denmark, the total annual number of prostatectomies increased by 43% during the 7-year peri od 1977-1985, and this trend was present in all age groups [3], Sejr et al [3] suggested that this large increase may indicate that patients who were previously consid ered inoperable with OP are now undergoing TURP, or that the indications for prostatectomy have been progres sively expanded.…”
Section: <0mentioning
confidence: 99%
See 1 more Smart Citation
“…Lange Zeit galt die operative Behandlung der BPH als alleiniger Goldstandard, wobei der Patientenselektion und dem langfristigen Erfolg nur wenig Aufmerksamkeit geschenkt wurde. Durch eine Reihe von Publikationen [2, 25,30] wurde zum einen auf die ü berraschende Variabilitä t der Operationszahlen bei einem ä hnlichen Patientengut hingewiesen. Eine Reihe weiterer Studien galt dem langfristigen Erfolg der verschiedenen operativen Eingriffe [5,11,26].…”
unclassified